Hubungan Konsumsi Sumber Protein, Lemak dan Riwayat Penyakit Infeksi dengan Balita Underweight Usia 12 – 59 Bulan di Kabupaten Seluma, Bengkulu: Relationship Between Protein, Fat Consumption and History of Infectious Diseases With Underweight Toddler Age 12 – 59 Months In Seluma District, Bengkulu - Karunia, Mekti; Arie Krisnasary; Desri Suryani; Kusdalinah (UNIVERSITAS NGUDI WALUYO, 2025)
The Indonesian Nutritional Status Study (SSGI) in 2022 showed that the prevalence of underweight is still quite high in Indonesia at (17.1%). Underweight or low body weight can be interpreted as a condition where infants or toddlers fail to achieve their ideal body weight. Having a nutritional status with a BB/U indicator on the threshold <˗2 SD. The main factors that cause underweight are inadequate food intake and infectious diseases. The aim of this research is to determine the relationship between consumption of protein, fat and history of infectious diseases with underweight toddlers aged 12 - 59 months in the working area of Cahaya Negeri Health Center, Seluma Regency in 2024. This research method uses analytical descriptive with a cross sectional approach with a sample size of 50 underweight toddlers. The data taken were protein and fat consumption data by interview using the Semi FFQ form, history of infectious diseases by interview using a questionnaire and body weight data carried out by directly weighing the toddlers. Statistical analysis uses the Pearson correlation test. The average protein consumption was 16.8 grams, the average fat consumption was 22.5 grams, the average history of infectious disease was 2 times in the last 3 months and the average z-score result was -2.2. Protein consumption was associated with underweight (p=0.000), fat consumption was associated with underweight (p=0.003) and a history of infectious disease was associated with underweight (p=0.001). There is a relationship between the consumption of protein, fat and a history of infectious diseases in underweight toddlers aged 12 - 59 months in the working area of Cahaya Negeri Health Center, Seluma Regency in 2024. There is a need to provide a nutritious menu for additional food and monitor growth and development in underweight toddlers. ABSTRAK Studi Status Gizi Indonesia (SSGI) 2022 menunjukan bahwa prevalensi underweight masih tergolong cukup tinggi di Indonesia sebesar (17,1%.). Underweight atau berat badan kurang dapat diartikan kondisi dimana anak bayi atau balita gagal dalam mencapai berat badan idealnya. Memiliki status gizi dengan indikator BB/U diambang batas < ˗2 SD. Faktor utama yang mengakibatkan underweight adalah asupan makanan yang kurang dan penyakit infeksi. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara konsumsi protein, lemak dan riwayat penyakit infeksi dengan balita underweight usia 12 – 59 bulan di wilayah kerja Puskesmas Cahaya Negeri Kabupaten Seluma tahun 2024. Metode penelitian ini menggunakan deskriptif analitik dengan pendekatan Cross Sectional dengan jumlah sampel sebanyak 50 balita dengan underweight. Data yang diambil adalah data konsumsi protein dan lemak dengan cara wawancara menggunakan formulir Semi FFQ, riwayat penyakit infeksi dengan cara wawacara menggunakan kuesioner serta data berat badan yang dilakukan dengan penimbangan langsung kepada balita. Analisis statistik menggunakan uji korelasi pearson. Rata rata konsumsi protein yaitu 16,8 gram, rata rata konsumsi lemak yaitu 22,5 gram, rata rata riwayat penyakit infeksi yaitu 2 kali dalam 3 bulan terakhir dan rata rata hasil z-skor yaitu -2,2. Konsumsi protein berhubungan dengan underweight ( p=0.000), konsumsi lemak berhubungan dengan underweight (p=0.003) dan riwayat penyakit infeksi berhubungan dengan underweight (p=0.001). Ada hubungan antara konsumsi protein, lemak dan riwayat penyakit infeksi dengan balita underweight usia 12 – 59 bulan di wilayah kerja Puskesmas Cahaya Negeri Kabupaten Seluma tahun 2024. Perlunya pemberian menu yang bergizi pada makanan tambahan dan pemantuan tumbuh kembang pada balita underweight.